1994
DOI: 10.1161/01.cir.90.4.1826
|View full text |Cite
|
Sign up to set email alerts
|

Power spectrum analysis of heart rate variability to assess the changes in sympathovagal balance during graded orthostatic tilt.

Abstract: Spectral analysis of HRV, using nu or LF-to-HF ratio, appears to be capable of providing a noninvasive quantitative evaluation of graded changes in the state of the sympathovagal balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
677
2
44

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 966 publications
(769 citation statements)
references
References 28 publications
46
677
2
44
Order By: Relevance
“…The normalisation of LF and HF was obtained by subtracting from total power the very low frequency component. This calculation is useful when evaluating the effects of different interventions in the same subject or when comparing subjects with major differences in total power [24].…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…The normalisation of LF and HF was obtained by subtracting from total power the very low frequency component. This calculation is useful when evaluating the effects of different interventions in the same subject or when comparing subjects with major differences in total power [24].…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Interestingly, previous studies have shown that a simple functional manoeuvre like slow deep-breathing can increase the BRS [17][18][19], an important and well-established prognostic index, and also reduce the sympathetic tone in conditions like heart failure, hypertension and chronic obstructive pulmonary disease [20][21][22]. In contrast, the upright posture increases sympathetic activity and reduces the BRS [23].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive experimental and clinical evidence has shown that high frequency (HF) is synchronous with the respiratory cycle and mainly supported by vagal activity, whereas low frequency (LF) is largely correlated with sympathetic efferent activity. [7][8][9] In the present study, we used HRV as a strategy to study the sympathetic and vagal controls during sustained handgrip exercise in obese individuals with 12Glu9 deletion polymorphism of the a 2B -AR gene. Previous investigations using HRV analysis [10][11][12][13][14] and measurements of plasma catecholamines 15,16 showed altered sympathetic responsiveness during cold exposure, spicy food containing capsaicin and glucose ingestion in obese individuals.…”
Section: Introductionmentioning
confidence: 99%